Anti-Sporotrichotic Activity, Lambert-W Inhibition Kinetics and 3D Structural Characterization of Sporothrix schenckii Catalase as Target of Glucosinolates from Moringa oleifera - Erick Sierra-Campos; Mónica A. Valdez-Solana; Estela Ruiz-Baca; Erica K. Ventura-García; Claudia I. Avitia-Domínguez; Miguel Aguilera-Ortiz; Alfredo Téllez-Valencia (MDPI AG, 2022)
Most human fungal infections exhibit significant defensive oxidative stress responses, which contribute to their pathogenicity. An important component of these reactions is the activation of catalase for detoxification. To discover new antifungal chemicals, the antifungal activity of methanol extracts of Moringa oleifera from two commercial products (Akuanandi and Mas Lait) was investigated. The methanolic extracts' activity against Sporothrix schenckii was determined using an assay for minimum inhibitory concentration (MIC) and minimum lethal concentration (MLC). The MIC concentrations varied between 0.5 μg/mL and 8 μg/mL. Akuanandi extract had the lowest MIC (0.5 μg/mL) and MLC (1 μg/mL) values. M. oleifera methanolic extracts were tested for catalase inhibition. The Ki values of the M. oleifera extract against S. schenckii catalase (SsCAT) was found to be 0.7 μg/mL for MOE-AK and 0.08 μg/mL for MOE-ML. Catalase's 3D structure in SsCAT is unknown. The homology of SsCAT was modeled with an in silico study using a 3D structure from SWISS MODEL and validation the predicted 3D structure was carried out using PROCHECK and MolProbity. Docking simulations were used to analyze protein interactions using Pymol, PoseView, and PLIP. The results revealed that M. oleifera glucosinolates interacts with SsCAT. A molecular interaction analysis revealed two inhibitor compounds (glucosinalbin and glucomoringin) with high binding affinity to key allosteric-site residues. The binding energies revealed that glucosinalbin and glucomoringin bind with high affinity to SsCAT (docking energy values: −9.8 and −9.0 kcal/mol, respectively). The findings of this study suggest that glucosinolates derived from M. oleifera could be used instead of synthetic fungicides to control S. schenckii infections. We hope that the findings of this work will be valuable for developing and testing novel natural anti-sporothrix therapeutic agents in the future.